The Impact of Artificial Intelligence on Perceived Trust and Purchase Intention on Shopee Among Generation Z - Wasilah, Qasimatul; Hartono, Arif (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Artificial Intelligence (AI) is a rapidly advancing technology that has seen widespread adoption across various sectors of the digital economy, including the e-commerce industry. This study aims to examine the influence of AI in fostering perceived trust and purchase intention among Generation Z users on the AI-integrated e-commerce platform Shopee. A quantitative research design was employed, utilizing an online questionnaire measured on a six-point Likert scale. The respondents consisted of 200 active Shopee users from Generation Z who are familiar with the platform’s AI-driven features. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 software. The model comprises three independent variables, namely AI exposure, attitude towards AI, and AI accuracy perception, as well as two mediating variables, namely perceived trust and perceived usefulness, and one dependent variable, purchase intention. The findings reveal that AI exposure, attitude towards AI, and AI accuracy perception each exert a positive and statistically significant effect on perceived trust. Moreover, perceived trust is shown to mediate the relationship between these three independent variables and purchase intention. Additionally, perceived usefulness functions as a mediating variable in the relationship between perceived trust and purchase intention.